Contributions of SRI Sukuk to SDGs: An Analysis of Selected Cases - Guedira, Souhaila; El Amri, Mohamed Cherif; Mohammed, Mustafa Omar; Elamrı, Mohamed Cherıf (Taylor and Francis, 2024)
SRI Sukuk are investment certificates conforming to Islamic law issued to finance and invest in projects that are concerned with social and environmental matters, in addition to providing financial benefits. With the increase in investors’ interest in SRI projects and the growth of SRI Sukuk issuance during the last decade, it is worthwhile to take a close look at some of those projects to analyse and discuss their social, environmental and green impacts. The available literature focuses mainly on the technical and financial characteristics and aspects of SRI Sukuk and their detailed schemes, with hardly any emphasis on their environmental, social and governance prints. This chapter adopts a qualitative analysis of some selected SRI Sukuk cases and their assessment in terms of social and environmental benefits. The chapter also indicates the links and the contribution to the SDG targets for each discussed case. The study provides insights for future empirical research on the topic and suggests important motivating factors for investors to consider SRI Sukuk projects for their investments.
Islamic Green Finance: A Research Companion / Editors:Mohd Ma'Sum Billah, Rusni Hassan, Razali Haron, Romzie Rosman, Akhtarun Naba’ Billah -- Taylor and Francis -- ISBN:978-104012106-1, 978-103267291-5 -- 2024.